Effect of Mindfulness Based Stress Reduction (MBSR) in Increasing Pain Tolerance and Improving the Mental Health of Injured Athletes - Mohammed, Warhel Asim; Pappous, Athanasios; Sharma, Dinkar (Frontiers in Psychology, 2018)
Abstract: Literature indicates that injured athletes face both physical and psychological distress after they have been injured. In this study, a Mindfulness Based Stress Reduction (MBSR) was utilised as an intervention for use during the period of recovery with injured athletes and, to the best of our knowledge, this is the first study using MBSR as an intervention for this purpose. Objective: The aim of this research was to investigate the role of MBSR practice in reducing the perception of pain and decreasing anxiety/stress, as well as increasing pain tolerance and mindfulness. An additional aim was to increase positive mood and decrease negative mood in injured athletes. Methods: The participants comprised of twenty athletes (male = 14; female = 6; age range = 21–36 years) who had severe injuries, preventing their participation in sport for more than three months. Prior to their injury, the participants had trained regularly with their University teams and participated in official university championships. Both groups followed their normal physiotherapy treatment, but in addition, the intervention group practised mindfulness meditation for 8 weeks (one 90-minute session/week). A Cold Pressor Test (CPT) was used to assess pain tolerance. In contrast, the perception of pain was measured using a Visual Analogue Scale. Other measurements used were the Mindful Attention Awareness Scale (MAAS), Depression Anxiety and Stress Scale (DASS), and Profile of Mood States (POMS). Results: Our results demonstrated an increase in pain tolerance for the intervention group and an increase in mindful awareness for injured athletes. Moreover, our findings observed a promising change in positive mood for both groups. Regarding the Stress/Anxiety scores, our findings showed a notable decrease across sessions; however, no significant changes were observed in other main and interaction effects in both groups. Conclusion: Injured athletes can benefit from using mindfulness as part of the sport rehabilitation process to increase their pain tolerance and awareness. Further research is required to assess whether increasing pain tolerance could help in the therapeutic process.